A Study On The Determinants Of Business Stability In Credit Card Firms: Evidence From Korea - Seo, Ji Yong (Asian Academy of Management (AAM), 2014)
This study empirically analyses several factors that affect financial stability such as the profitability of Korean credit card firms, capital adequacy, loan soundness, and liquidity. In particular, internal and external factors found in previous studies were applied to the analysis in order to investigate whether or not those factors had a significant effect on the business stability of Korean credit card firms. The major research findings are as follows. First, the determinant factors for profitability were found to be the degree of enlargement, foreign credibility, and the level of risk management. Second, the determinant factors for capital adequacy were found to be the degree of enlargement, diversification, foreign credibility, the level of management, and the interest rate. Third, the determinant factors for loan soundness were found to be the degree of enlargement and foreign credibility. Lastly, the determinant factors for liquidity were found to be the degree of diversification, foreign credibility, the level of risk management, the degree of competition, economic conditions, and the interest rate. In conclusion, with the recent reduction in the card affiliates’ fees, the leverage regulation, and the credit card debt suppression policy, financial authorities will likely refer to this study as they carefully examine the various influences on the business stability of domestic credit card firms and come up with relevant countermeasures for the continuous growth of those firms.